IJSD Volume 8 2017 Solo/Screen: Full Issue - Harmony Bench; Simon Ellis (The International Journal of Screendance, 2017)
The full issue of IJSD vol. 8 (2017). Please note: For the best offline reading experience, please print double-sided on 8.5x11 paper. Links to online sources are live in the PDF if read onscreen.
Keywords: The International Journal of Screendance; volume 8; screendance; solo performance